The wisdom of the bullfrog [large type] : leadership made simple (but not easy) - McRaven, William H. (William Harry), 1955- (Grand Central Publishing, 2023)
"From the acclaimed, #1 New York Times bestselling author of Make Your Bed, a short, inspirational book of advice and leadership lessons that Admiral McRaven collected over his four decades as a Navy SEAL"--